School in the (im)possibility of future: Utopia and its territorialities - Grinberg, Silvia Mariela (2018)
Utopia makes itself heard as Raphael voices a critique of who we are and configures that no-where which, paradoxically, we want to reach. We look to Deleuze and Guattari when we say that that critique can be envisioned as resistance to the present. In the passage from no-where to now-here, we revisit the territories of utopia as critique of our times, as a way to approach the question of who we are and who we want to be. In our view, education still rests on the image of a future that unfolds in the encounter with others. Education and its need/potential to enable tomorrows, to invent promises that look to places of desire, spaces that take shape as heterotopias. The notion of utopia is strained at root because defined as a no-where. At school, it is bound to the potential to create new possibilities and alternatives for life in the here and now. In this article, we will grapple with the work we do in university classrooms and in educational institutions in the slums on the outskirts of the city of Buenos Aires as a gateway from which to envision and to problematize the world. From there, we will approach the voices where other possibilities are conquered and other spaces created on the basis of the unpredictable, voices rooted in education and the need for it that produce and produce themselves in the tensions of that (im)possibility. In sum, wording the world as creation of worlds.